Terrorist Attacks on Non-Governmental Organizations - Stapley, Craig S. (My University, 2014)
Understanding the process by which terrorist groups decide on whom to target would seem to be a process that might lend itself to study and generalization that would be helpful in predicting later attacks. This study hopes to look at the attacks on non-governmental organizations and determine if there is a systematic set of measures that would allow us to determine if terrorist groups do rationally approach target selection in such a way to derive a pattern that would inform future attack avoidance.
Citation: Stapley, C. S. (2014). Terrorist Attacks on Non-Governmental Organizations. Open Journal of Political Science, 04, 265. https://doi.org/10.4236/ojps.2014.44029
Keywords: Terrorism; Targeting; NGO; Non-Governmental Organization; Terrorist